5‐Hydroxymethylcytosine as a clinical biomarker: Fluorescence‐based assay for high‐throughput epigenetic quantification in human tissues. Issue 1 (2nd July 2019) - Margalit, Sapir; Avraham, Sigal; Shahal, Tamar; Michaeli, Yael; Gilat, Noa; Magod, Prerna; Caspi, Michal; Loewenstein, Shelly; Lahat, Guy; Friedmann‐Morvinski, Dinorah; Kariv, Revital; Rosin‐Arbesfeld, Rina; et al.
Abstract : Epigenetic transformations may provide early indicators for cancer and other disease. Specifically, the amount of genomic 5‐hydroxymethylcytosine (5‐hmC) was shown to be globally reduced in a wide range of cancers. The integration of this global biomarker into diagnostic workflows is hampered by the limitations of current 5‐hmC quantification methods. Here we present and validate a fluorescence‐based platform for high‐throughput and cost‐effective quantification of global genomic 5‐hmC levels. We utilized the assay to characterize cancerous tissues based on their 5‐hmC content, and observed a pronounced reduction in 5‐hmC level in various cancer types. We present data for glioblastoma, colorectal cancer, multiple myeloma, chronic lymphocytic leukemia and pancreatic cancer, compared to corresponding controls. Potentially, the technique could also be used to follow response to treatment for personalized treatment selection. We present initial proof‐of‐concept data for treatment of familial adenomatous polyposis. Abstract : What's new? The amount of genomic 5‐hydroxymethylcytosine (5‐hmC) was shown to be globally reduced in a wide range of cancerous tissues. The utility of such an epigenetic transformation as a clinical biomarker is hampered by the limitations of existing detection assays, however. The authors present a simple‐to‐perform fluorescence‐based platform for high‐throughput and cost‐effective quantification of global genomic 5‐hmC levels. They demonstrate the assay's sensitivity in detecting various cancers and its applicability for colorectal cancer diagnosis. Potentially, the technique could also be used to follow response to treatment for personalized treatment selection, with the authors providing initial proof‐of‐concept data for familial adenomatous polyposis.